On a PsÐµuÔo Smarandache Ideals of BH-algebra - Hadi Abbass, Husein; Abdulhussein Jabbar, Ahmed (International Journal of Engineering and Technology, 2018)
In this paper the notion of a pseudo Samarandache BH-algebra, a psÒ½uÔo Samarandache ideal, a psÒ½udo Smarandache closed ideal andÂ  a psÒ½udo Samarandache completely closed ideal of a pseudo Samarandache BH-algebra are defined. There notion are stadied. The relationships among these types of ideals are discussed.Â